The norms of answerability : social theory between Bakhtin and Habermas - Nielsen, Greg Marc, 1953- (State University of New York Press, 2002)
Annotation Greg M. Nielsen brings Mikhail Bakhtin's ethics and aesthetics into a dialogue with social theory that responds to the sense of ambivalence and uncertainty at the core of modern societies. Nielsen situates a social theory between Bakhtin's norms of answerability and Jurgen Habermas's sociology, ethics, and discourse theory of democracy in a way that emphasizes the creative dimension in social action without reducing explanation to the emotional and volitional impulse of the individual or collective actor. Some of the classical sources that support this mediated position are traced to Alexander Vvedenskij's and Georg Simmel's critiques of Kant's ethics, Hermann Cohen's philosophy of fellowship, and Max Weber's and George Herbert Mead's theories of action. In the shift from Bakhtin's theory of interpersonal relations to a dialogic theory of societal events that defends the bold claim that law and politics should not be completely separated from the specificity of ethical and cultural communities, a study of citizenship and national identity is developed. Book jacket.
Keywords: Social norms.; Sociology -- History.; Normes sociales.; Sociologie -- Histoire.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Social norms; Sociology; Sociale normen.; Sociologie.; Ethiek.; Theorieën.; History